Neuro-Immune Hemostasis: Homeostasis and Diseases in the Central Nervous System - De Luca, Ciro; Colangelo, Anna Maria; Alberghina, Lilia; Papa, Michele (Frontiers in Cellular Neuroscience, 2018)
Coagulation and complement cascades interact in several physiological and pathological conditions, including tissue repair and immune responses. This network plays a key role in diseases of the Central Nervous System (CNS) by involving cells (CNS resident cells, platelets, endothelium, and leukocytes) and molecular pathways (protease activity, complement factors, platelet granule content). Endothelial damage prompts platelet activation and the coagulation cascade as the first physiological step to support the rescue of damaged tissues, a flawed rescuing system ultimately producing neuroinflammation. Platelets, indeed, can release chemokines and cytokines (platelet factor 4, CXCL4), and growth factors including platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and brain-derived neurotrophic factor (BDNF). Thrombin, plasmin, and matrix metalloproteinase-1 (MMP-1), furthermore, activate intracellular transduction through protease-activated receptors (PARs). The complement cascade sustains the cellular response to insults by activating the innate immune system and guiding leukocytes migration or differentiation. Impairment of the neuro-immune hemostasis network induces acute or chronic CNS pathologies related to the neurovascular unit, either directly or by the systemic activation of its main steps. Glial cells (astrocytes and microglia) and the extracellular matrix (ECM) play a crucial function in a “pentapartite” synaptic model. Taking into account the neurovascular unit, in this review we thoroughly analyzed the influence of neuro-immune hemostasis on these five elements acting as a functional unit (synapse) in the adaptive and maladaptive plasticity and discuss the relevance of these events in inflammatory, cerebrovascular, Alzheimer, neoplastic and psychiatric diseases. Finally, we show a solid neuro-immune hemostatic network based on protein-protein interactions. We propose that, to better understand and favor the maintenance of adaptive plasticity, it would be useful to construct predictive molecular models, able to enlighten the regulating logic of the complex molecular network, which belongs to different cellular domains. It would be of interest to define how nodes of the network interact with basic cellular functions, such as mitochondrial metabolism, autophagy or apoptosis. It is expected that dynamic systems biology models might help to elucidate the fine structure of molecular events generated by blood coagulation and neuro-immune responses in several CNS diseases, thereby opening the way to more effective treatments.